Sukoharjo, Warehouse of Herbal Plants with Stunning Ethnobotanical Wealth: Exploration, Utilization, and Preservation of Local Knowledge - Septianingrum, Parigi Akhiri; Purwanto, Agus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The existence of local herbal plants that are rich in ethnobotanical properties should be a strong foundation in the development of public health based on local wisdom and the modern herbal industry. However, in reality, many types of plants with high efficacy have not been well documented, and the practice of using them is still hereditary without a deep scientific approach. This study aims to document and analyze the use of traditional medicinal plants in Brongsongan Hamlet, Sukoharjo. This study is a qualitative descriptive study with an ethnobotanical approach. A total of eleven types of medicinal plants that are still used by the local community were identified, including Moringa oleifera (moringa leaves), Amomum compactum (Javanese cardamom), Kaempferia galanga (galangal), Piper betle L. (betel leaf), Andrographis paniculata (sampiloto), Piper sarmentosum (karuk), Cymbopogon citratus (lemongrass), Curcuma longa (turmeric), Ambrosia trifida (insulin leaves), Carica papaya folium (papaya leaves), and Morinda citrifolia (mengkudu). The local community uses these plants as part of traditional medicine and for daily health maintenance. This study recommends more systematic documentation, community education, and the use of digital technology to support the preservation and sustainable use of medicinal plants.